Production of omega-3 fatty acid from Nannochloropsis Sp. on the effects of carbon dioxide and light intensity - Nor Farahiyah, Ghazali (2012)
Omega-3 polyunsaturated fatty acid PUFA) plays a vital role in a number of human health aspects substantially for the regulation of biological function,prevention and treatment of human diseases. Subsequently,humans cannot synthesize the omega-3 PUFA,eicosapentaenoic acid(EPA)and docosahexaenoic acid(DHA),thus,intake comes predominantly from dietary. Therefore,the microalgae was discovered as an alternative source of fatty acids compared to fish oil since it offers better purification essential and has no risk of chemical contamination.Moreover,it also acts as a carbon dioxide fixer by photosynthesis process in reducing the atmospheric carbon dioxide.There are major factors give affect for microalgae growth which is carbon source,irradiance level, temperature,nutrient availability and salinity.This study is carried out to investigate carbon dioxide effect in the specific range of 2%, 5%, 10% and 15% at flow rate of 0.2 L/min.Meanwhile,the irradiance levels are examined by using 31 µmol photons m-2 s-1, 82 µmol photons m-2 s-1 ,125 µmol photons m-2 s-1 and 156 µmol photons m-2 s-1 by applying one factor at time (OFAT) in maximizing the production of omega-3 fatty acids.The microalgae of Nannochloropsis sp.are cultured in f/2 medium with 300 ml working volume for 7 days of cultivation in an experimental system of photobioreactor.The omega-3 fatty acid compositions of Nannochloropsis sp.under different culture conditions are analyzed by lipid extraction and gas chromatography analysis in order to acquire the maximum amount of yield production.The results showed that the highest eicosapentaenoic acid productivity by Nannochloropsis sp.had been obtained at 2% of carbon dioxide aeration and 156 µmol photons m-2 s-1 which are 31.3121 mg/ml and 35.1339 mg/ml, respectively. The fatty acid accumulation of Nannochloropsis sp.could be prevailed to produce a high yield under their optimal conditions which are in maximal efficiency of carbon dioxide and high of light intensity.